The verbs of common lexical layer in the texts of scientific style "аcoustics and ultrasonics" - Dyachenko, G. F.; Дьяченко, Галина Федорівна; Дьяченко, Г. Ф.; Tsynovaya, M. V.; Цинова, Марина Вікторівна; Цинова, М. В.; Sirotenko, T. V.; Сиротенко, Тетяна Володимирівна; Сиротенко, Т. В. (Одеса, 2017)
Стаття подає опис результатів аналізу лексичних, статистичних і семантичних особливостей дієслів, які входять у загальновживаний шар лексики. Матеріалом для текстового корпусу «Акустика й ультразвукова техніка» послугували статті з наукових журналів США та Великої Британії.

The paper represents the description of the results of analysis of lexical, statistical and semantic features of the verbs in common lexical layer. The text corpus "Acoustics and Ultrasonics" is based on the articles from scientific journals of the USA and Great Britain.
Dyachenko G. F. The verbs of common lexical layer in the texts of scientific style "аcoustics and ultrasonics" / G. F. Dyachenko, M. V. Tsynovaya, T. V. Sirotenko // Одеський лінгвістичний вісник. – 2017. – Вип. 9. – Т.1. – С. 60-65.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; лексико-семантична група; багатозначне дієслово; слововживання; стратифікаційний шар; lexical-semantic group; polysemous word; stratification layer; word token